2007
DOI: 10.1080/00049180701399985
|View full text |Cite
|
Sign up to set email alerts
|

Factors Inhibiting Local Government Engagement in Environmental Sustainability: case studies from rural Australia

Abstract: The literature on local government management of the environment in Australia has been limited in that it has typically focused on the urban sphere. In contrast, this paper places rurality at the centre of its inquiry. It uses data from 15 case studies of rural local governments in Australia to identify the main factors that inhibit natural resource management by rural councils. These barriers mobilise around four key themes: capacity, commitment, co-ordination and community. While many of the issues raised in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…Municipalities are frequently highly constrained in terms of their financial capacity (Pini et al 2007). In part this stems from the wide range of activities in which they are engaged.…”
Section: Resource Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Municipalities are frequently highly constrained in terms of their financial capacity (Pini et al 2007). In part this stems from the wide range of activities in which they are engaged.…”
Section: Resource Constraintsmentioning
confidence: 99%
“…Crabbé and Robin (2006) comment that the issue of climate change appears 'distant and cloudy' amongst an already crowded agenda of demands placed on local government by concerned citizens. Even in a single locality, the mandate of municipalities frequently extends from aesthetics to infrastructure, from parking to waste management (Wild River 2006;Pini et al 2007). Furthermore, the mandate of local government is expanding, due to the shifting of responsibility from higher levels of authority to lower levels of authority, particularly from state and provincial authorities (Ivey et al 2004).…”
mentioning
confidence: 99%
“…In fact, in the context of development, people who use the input of energy, materials and technology to carry out daily activities in a city could create urban ecosystem deterioration intentionally or unintentionally (Jahi, 1996;Hussain & Ismail, 2013). Even everyday activities by human development in a town have created too much problems to the ecosystem despite the positive impact of the development (Hassan, Awang, & Jaafar, 2006;Pini, River, & McKenzie, 2007;Subhan, Ghani, & Joarder, 2014). The beneficial effects left by urban development such as an opportunity increase to quality of life, economic growth and physical development of urban city are certainly needed by society.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several studies have identified that the serious barriers to adaptation are institutional in nature Waters et al 2014). Using the definition of of institutions in the CCA context, the following barriers or challenges were identified (1) factors influenced by rule-based institutions such as autonomy of local governments, local government prioritisation, commitment to CCA, and other institutional issues relating to policies, regulations, and the like (Pini et al 2007;OECD 2009;Burch 2010;Ayers et al 2014;Waters et al 2014); (2) matters linked to social structure-based institutions such as community support, institutional incentives and local leadership (Burch 2010;Moser & Ekstrom 2010;Biesbroek et al 2011;and (3) organisational concerns like organisational cohesion, and organisational cooperation and collaboration arrangements (Pini et al 2007;Amundsen et al 2010;Biesbroek et al 2011;Eisenack et al 2014). …”
Section: The Iad-cca Frameworkmentioning
confidence: 99%
“…These include the (1) extent of knowledge and awareness of climate change issues; (2) availability, accessibility, credibility, and reliability of information; (3) manner by which information is communicated and translated by climate change experts; and (4) way the information is received by the users (i.e., planners and decision-makers) (Ekstrom et al 2011;Ayers et al 2014;. Meanwhile, resource constraints have always been a problem for local governments; however, they are highlighted in CCA because resources are crucial factors of adaptive capacity (Pini et al 2007;Biesbroek et al 2011). For example, lack of funds is typically among the primary reasons why the implementation of local adaptation is delayed (Moser & Ekstrom 2010;Lehmann et al 2015).…”
mentioning
confidence: 99%